Electrochemiluminescence Detection of Sunset Yellow by Graphene Quantum Dots - Huimin Niu; Xin Yang; Yilei Wang; Mingchen Li; Guangliang Zhang; Peng Pan; Yangyang Qi; Zhengchun Yang; John Wang; Zhenyu Liao; Zhenyu Liao (Frontiers in Chemistry, 2020)
Use of food additives, such as colorants and preservatives, is highly regulated because of their potential health risks to humans. Therefore, it is important to detect these compounds effectively to ensure conformance with industrial standards and to mitigate risk. In this paper, we describe the preparation and performance of an ultrasensitive electrochemiluminescence (ECL) sensor for detecting a key food additive, sunset yellow. The sensor uses graphene quantum dots (GQDs) as the luminescent agent and potassium persulfate as the co-reactant. Strong and sensitive ECL signals are generated in response to trace amounts of added sunset yellow. A detection limit (signal-to-noise ratio = 3) of 7.6 nM and a wide linear range from 2.5 nM to 25 μM are demonstrated. A further advantage of the method is that the luminescent reagents can be recycled, indicating that the method is sustainable, in addition to being simple and highly sensitive.